Before and After the Economic Growth, Regulatory Relief and Consumer Protection Act of 2018 - Dancer, W. Terry; Powell, Dwayne (Journal of Accounting and Finance, 2022)
The Dodd-Frank Wall Street Reform and Consumer Protection Act became law on July 21, 2010. The law was enacted to provide at least a modicum of regulation to the financial industry following the recession of 2008, leading to what some called the worst economic downturn in the United States Economy since the Great Depression. On May 24, 2018, President Trump signed S. 2155, The Economic Growth, regulatory relief, and Consumer Protection Act (the Relief Act). Many believe this new law put an end to Dodd-Frank. Others believe the new law did nothing to repeal and replace Dodd-Frank. In a prior study, the authors asked community bankers, “How will your day-to-day activities change if Dodd-Frank is repealed?” This paper follows up with a survey of community bankers to determine if S. 2155 had the expected results. This study finds that the Relief Act did not have the anticipated impact.